Phosphorus removal coupled to bioenergy production by three cyanobacterial isolates in a biofilm dynamic growth system. Issue 9 (1st September 2016) - Gismondi, Alessandra; Pippo, Francesca Di; Bruno, Laura; Antonaroli, Simonetta; Congestri, Roberta
ABSTRACT: In the present study a closed incubator, designed for biofilm growth on artificial substrata, was used to grow three isolates of biofilm-forming heterocytous cyanobacteria using an artificial wastewater secondary effluent as the culture medium. We evaluated biofilm efficiency in removing phosphorus, by simulating biofilm-based tertiary wastewater treatment and coupled this process with biodiesel production from the developed biomass. The three strains were able to grow in the synthetic medium and remove phosphorus in percentages, between 6 and 43%, which varied between strains and also among each strain according to the biofilm growth phase. Calothrix sp. biofilm turned out to be a good candidate for tertiary treatment, showing phosphorus reducing capacity (during the exponential biofilm growth) at the regulatory level for the treated effluent water being discharged into natural water systems. Besides phosphorus removal, the three cyanobacterial biofilms produced high quality lipids, whose profile showed promising chemical stability and combustion behavior. Further integration of the proposed processes could include the integration of oil extracted from these cyanobacterial biofilms with microalgal oil known for high monounsaturated fatty acids content, in order to enhance biodiesel cold flow characteristics.